Marketing places and spaces - Correia, Anto<U+0301>nia (Advances in culture, tourism and hospitality research, 2015)
Marketing places and spaces covers a broad range of issues that hospitality and tourism executives will benefit from addressing, but frequently forget to do so. To provide an indication of the broad range and exciting coverage of issues, here are a few titles of the 21 chapters in the volume: Conceptualizing the Value Co-creation Challenges for Tourist Destinations: a Supply-Side Perspective; The Emotional Attachment Built through the Attitudes and Managerial Approach to Place Marketing and Branding - The Golden City of Kremnica, Slovakia; Events as a Differentiation Strategy for Tourist Destinations; How do Tourists Turn Space into Place? - A Conceptualisation for Sustainable Place Marketing; the Influence of Slow City in the Context of Sustainable Destination Marketing; Wedding-based Tourism Development: Insights from an Italian Context. Authors include tourism researchers working in Finland, UK, Macau, Japan, New Zealand, and beyond. A practical strategy guide and an in-depth complement with extensions to Elizabeth Gilbert's "Eat Pray Love" for hospitality and tourism professionals and educators is the relevant perspective that "Marketing Places and Spaces" provides.